Anatomy and embryology of fish liver and pancreas with a focus on their use in research - Fiala, E; Shoeib, MB; Ebada, S; Abdellatif, A (Journal of the Hellenic Veterinary Medical Society, 2026)
Fish liver and pancreas perform indispensable roles related to food digestion, metabolism, and glucose homeostasis. Both organs have been reported to share several anatomical, developmental, and regenerative mechanisms with those of higher vertebrates, including humans. These shared similarities made them a target of numerous experimental research studies. In this article, we summarize the anatomical, histological, and developmental features involving the liver and pancreas in fish. We also discuss strengths and weaknesses of their use for disease modelling.